1994
DOI: 10.1021/j100056a008
|View full text |Cite
|
Sign up to set email alerts
|

An MP2/6-31G*//MP2/6-31G* vibrational analysis of s-trans- and s-cis-acryloyl fluoride, CH2=CH-CF=O

Abstract: The MP2/6-3 lG*//MP2/6-3 l G * harmonic force fields are calculated for s-trans-and s-cis-acryloyl fluoride. The scale factors for the quantum mechanical force field of s-trans-acryloyl fluoride are optimized using the experimental vibrational frequencies. The set of scale factors obtained is then transferred to the computed MP2/6-31G*//MP2/6-3 l G * force field of thes-cis rotational isomer. Thevibrationalfrequencies arecomputed using the corresponding scaled quantum mechanical force fields and compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…A significant advent in this area was made by the scaled quantum mechanical (SQM) force field method [5][6][7][8]. In the SQM approach, the systematic errors of the computed harmonic force field are corrected by a few scale factors which were found to be well transferable between chemically related molecules [4,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…A significant advent in this area was made by the scaled quantum mechanical (SQM) force field method [5][6][7][8]. In the SQM approach, the systematic errors of the computed harmonic force field are corrected by a few scale factors which were found to be well transferable between chemically related molecules [4,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The additional experimental information available about the 532 cm-I band is only its depolarized character. 7. LO=C-C in-pl.…”
Section: Table 4 Scale Factors For Force Fields Of S-trans-and S-cis-mentioning
confidence: 99%
“…Their assignments were assisted by comparison of the experimental spectra with theoretically calculated harmonic vibrational frequencies obtained with ab initio calculations at 3-21G and 6-31G* basis set levels.2 These basis sets do not take correlation energy into account. It has been shown that second-order Moller-Plesset perturbation theory4 (MP2) using a split-valence basis set which includes d-type polarization functions on the heavy atoms can adequately predict the values of the experimental band frequencies for vibrations with low anharmonicity (for examples, see refs [5][6][7]. Thus it is expected that the results of MP2/6-31G*// MP2/6-31G* vibrational analyses on the 2-fluoropropenyl fluoride rotamers would be fairly reliable and instructive.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] A significant advancement in this area was made by combining semi-empirical quantum mechanical method, ab initio quantum mechanical method, and DFT, each method having its own advantage. [3 -6] In the scaled quantum mechanical (SQM) approach, the systematic errors of the computed harmonic force field are corrected by a few scale factors which are found to be well transferable between chemically related molecules [2,7,8] and were recommended for general use. The vibrational analysis of FNT using the SQM force field method based on DFT calculation has been presented.…”
Section: Introductionmentioning
confidence: 99%